Pharmacovigilance: A Review - Patel, Avani (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTAt an ever-growing scale people are using newer and more effective drugs with various medical conditions which are being manufactured with developing scientific advances. Safety and efficacy are the two major concerns about any drug. Now a day’s significance of pharmacovigilance is growing and with the contemporary high-profile drug extractions by the regulatory agencies, consumers and others have become more responsive about the advantage and hazards of remedies.